EVALUASI TINGKAT PELAYANAN RESERVOIR PDAM KABUPATEN PULAU MOROTAI AREA LAYANAN KECAMATAN MOROTAI SELATAN - Alam, Iradat; Khaerudin, Dian Noorvy (eUREKA : Jurnal Penelitian Teknik Sipil dan Teknik Kimia, 2019)
Clean water management in South Morotai District is managed by the Morotai Island District PDAM. The volume of the reservoir in the service area of South Morotai District is 450 m3 with a capacity of 25 liters/second sourced from the mangere spring. This study aims to determine the current reservoir capacity whether it is still able to meet the increasing demand for clean water throughout the year based on the projected population from 2017-2027. The population of the South Morotai District Service area in 2017 is 9.336 people. The projection of the population until 2027 is 19.371 people. Reviewed from the large production capacity of PDAM, the service area of South Morotai District has been able to meet the total customer needs of 8.018 liters / second in 2017 and 16.697 liters / second in 2027. Reservoir has not been able to serve customers' needs 24 hours a day, because water cannot be flowed continuously. This is because the reservoir volume is much smaller than the total needs of 735 m3 customers in 2017 and 1.443 m3 in 2027. For this reason, there must be a development of an increase in reservoir volume of 1.600 m3 in order to fulfill all customer requirements that are adjusted to the management criteria for clean water from Ditjen Cipta Karya PU 1996.